2013
DOI: 10.1080/13546805.2012.698239
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and social functioning in first episode psychosis

Abstract: Theory of mind assessed by verbal stimuli is associated with social functioning in a population with first episode psychosis. These findings may be related to language disorders in psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…This is consistent with Sullivan et al’s [ 14 ] finding that ToM does not predict poor outcomes longitudinally in the early stages of psychosis. The findings, however, are in contrast to other cross-sectional research which has found that ToM deficits are associated with poor social functioning in both early [ 13 ] and chronic psychosis [ 10 ]. These divergent findings may reflect differences in methodology.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is consistent with Sullivan et al’s [ 14 ] finding that ToM does not predict poor outcomes longitudinally in the early stages of psychosis. The findings, however, are in contrast to other cross-sectional research which has found that ToM deficits are associated with poor social functioning in both early [ 13 ] and chronic psychosis [ 10 ]. These divergent findings may reflect differences in methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…To address these issues, Sullivan et al [ 13 ] recently examined the relations between ToM, general cognition, symptoms and social functioning in a sample of patients in their first psychotic episode. Sullivan et al found that social functioning in their sample was associated with ToM (as measured by the Hinting task) and verbal IQ, but not with other general cognitive measures or a measure of negative symptoms that excluded symptoms that overlapped with poor social functioning (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, attributing overly complex mental states to others (Montag et al, 2011; Fretland et al, 2015), or overmentalizing, has been connected to positive symptoms of schizophrenia. Suspiciousness and delusions of persecution were found to be significant predictors of poor social functioning, and poor ToM performance (Hinting Test, Corcoran et al, 1995, Visual Cartoon Test, Corcoran et al, 1997) also plays a role in this relationship (Sullivan et al, 2013). However, other investigators using the Reading the Mind in the Eye Test (Baron-Cohen et al, 2001) found no connection between symptoms of schizophrenia and ToM (Kazemian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has accumulated suggesting deficits in discrete metacognitive processes, such as Theory of Mind, are present in FEP [e.g. 14,15].…”
Section: Introductionmentioning
confidence: 99%